Analysis of Agro-Industry Supply Chain Performance on Organic Rice in Jember Regency - Baladraf, Thabed Tholib (Agroindustrial Journal, 2024)
Organic rice is one of the potential food commodity innovations, organic rice has increased interest and demand from the market but is not matched with organic rice productivity. Based on this, analyzing the supply chain to determine performance and recommend improvement strategies is necessary. The purpose of this research is to determine the current organic rice supply chain system, analyze supply chain performance, and develop strategies to improve the performance of the organic rice agroindustry supply chain in Jember Regency. The method used in this research is supply chain performance analysis using supply chain operation reference (SCOR) and strategy formulation using analytical network process and benefit opportunity cost risk (ANP-BOCR). These methods were chosen because they synergize with each other and have been widely used in previous studies to analyze similar problems. The results showed that the performance of the organic rice agroindustry supply chain in Jember Regency received a score of 66.01 or classified into the average range. Hence, there is a need for improvement in the supply chain that is carried out through strategy. The results show that the sub-criteria benefit (0.198205), opportunity (0.164375), and economic (0.109545) get the highest value. Based on the results of pairwise comparisons, it is also found that the most appropriate strategy is to improve all KPIs.